2005
DOI: 10.1021/jp0535339
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics of Excited-State Intramolecular Proton Transfer around a Three-State Conical Intersection in Malonaldehyde

Abstract: Excited-state potential energy surface (PES) characterization is carried out at the CASSCF and MRSDCI levels, followed by ab initio dynamics simulation of excited-state intramolecular proton transfer (ESIPT) on the S2(pipi*) state in malonaldehyde. The proton-transfer transition state lies close to an S2/S1 conical intersection, leading to substantial coupling of proton transfer with electronic relaxation. Proton exchange proceeds freely on S2, but its duration is limited by competition with twisting out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 63 publications
8
117
1
Order By: Relevance
“…Ab-initio molecular dynamic simulation on MA has revealed that there are two pathways from the initially populated S 2 state, one being in-plane evolution followed by reversible proton exchange and finally populating the S 1 state through a nearby S 2 /S 1 conical intersection. 35 The second path includes a torsion about the CC bond that opens up the chelate ring providing efficient quenching to both S 1 and S 0 . A balance between these two pathways is expected to influence the repopulation of S 0 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ab-initio molecular dynamic simulation on MA has revealed that there are two pathways from the initially populated S 2 state, one being in-plane evolution followed by reversible proton exchange and finally populating the S 1 state through a nearby S 2 /S 1 conical intersection. 35 The second path includes a torsion about the CC bond that opens up the chelate ring providing efficient quenching to both S 1 and S 0 . A balance between these two pathways is expected to influence the repopulation of S 0 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Symmetry required CoIns involving three states have been early recognized. [236][237][238][239] However, the presence of accidental CoIns involving three states and its role in the photochemistry (see also Section 3.3.1) is emerging only now [240][241][242][243][244][245][246][247] and it will be subject of intensive investigation in the coming years. Accidental CoIns involving four states are much more recent.…”
Section: Nonadiabatic Photochemistrymentioning
confidence: 99%
“…The dramatic enhancement of experimental resolution has been paralleled by a steady increase in computing power, accelerating theoretical study [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. One of the most popular molecular 'families' for studying ESIPT has been salicylic acid and its derivatives [5,[10][11][12][14][15][16][17][18][19][20]24,26,27,[32][33][34][35][36], and we have previously presented computational analyses of the phenomenon in malonaldehyde (MA) [14,37] and methyl salicylate (MS) [15]. Here we examine salicylaldehyde, more commonly known as o-hydroxybenzaldehyde (OHBA).…”
Section: Introductionmentioning
confidence: 99%
“…Here we examine salicylaldehyde, more commonly known as o-hydroxybenzaldehyde (OHBA). As shown in Figure 1, OHBA and MS differ only in substitution of a methoxy for a hydroxy group, while MA represents the bare ESIPT reaction center present in each of the other two (and in all members of the salicylic acid family, see Figure 1 of reference 14).…”
Section: Introductionmentioning
confidence: 99%